Penguasaan dan Pemilikan Tanah yang Diskriminatif: dalam Perspektif Hukum Internasional dan Hukum Nasional - Jawahir Thontowi (Fakultas Hukum Universitas Islam Indonesia, 2000)
This essay reveals that indigenous people such as Indian people in America^and Aborigine in Australia find it dificult to culturally and socially Integrate with white people who are colonizers. Some cases of state conflict relating to the land dispute have placeda vital role in which neighbors countries are involved in the arms conflict or wars. It is not be cause the absence of the law to handle dispute, rather the political interest of certain country predominate to treat the case unjustly as demonstrated in Palestine case. In relation to the current situation, the Australian and Indonesian government concern very much to improve land reform for the interest of the people by is suing certain laws andregulations. In fact, however, the Australian government currently recognizes the Native Title Act for Aborigine to occupy and own their own land in conjuction with their own beliefs' and myths. The positive development takes place in Indonesian, not only, because the presence of the state platform of guideline and the law No 22/1999 concerning the local autonomy, but also due to the people welfare, the government requires to implement thebasic principle of agrarian law. It is in fact, however, uneasy to implement it because the practice ofthe state of local autonomy is challenged by internal problems of professional workers and also in certain territories, such as Yogyakarta, is uneasy to fully adhere the law because of its special treatment.